2012
DOI: 10.4103/1947-2714.98586
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of gallbladder cancer

Abstract: Gallbladder cancer (GBC) is a rather uncommon disease, but at the time when it gives symptoms it has usually reached no longer curable stage. Therefore, all attempts must be made to make the diagnosis earlier to have better opportunity for cure. The author searched PubMed, and reviewed literatures on diagnoses and treatment of GBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 54 publications
2
64
0
1
Order By: Relevance
“…Recently, several studies suggested GB polyps greater than 10 mm detected only on US, with 18 F-FDG uptake, old age, and large size are risk factors for malignancy [8,11,12]. In clinical series, surgery has been recommended for symptomatic GB polyps that are 6 mm or greater, and in patients at risk of malignancy, such as those older than 60 years, and for patients with GB polyps with diameters greater than 10 mm [3,13,14]. However, a large number of GB polyps greater than 10 mm have been found to be benign [8,12,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies suggested GB polyps greater than 10 mm detected only on US, with 18 F-FDG uptake, old age, and large size are risk factors for malignancy [8,11,12]. In clinical series, surgery has been recommended for symptomatic GB polyps that are 6 mm or greater, and in patients at risk of malignancy, such as those older than 60 years, and for patients with GB polyps with diameters greater than 10 mm [3,13,14]. However, a large number of GB polyps greater than 10 mm have been found to be benign [8,12,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…[18] This strengthens the hyperplasia-dysplasia-carcinoma progression hypothesis of a biliary carcinogenesis mechanism. [2223] The Roux-en-Y technique is the one expected to produce lower rates of cholangitis because it is immune to pancreatic reflux and less prone to intestinal bacterial backflow because of the protective action exerted by the interposed jejunal loop. Tocchi[21] reported a retrospective study of 1003 patients who underwent biliary enteric anastomosis (transduodenal sphincteroplasty, CDS, and HJS) for benign disease with 129.6 years mean follow-up: Univariate and multivariate analysis showed a significantly higher incidence of cholangiocarcinoma in the CDS group ( P = 0.02), and cholangitis was confirmed to be the only independent factor affecting its incidence ( P = 0.001, odds ratio 35.7).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on GBC are far more limited. At the moment, only the expression of Notch receptors (1)(2)(3)(4) and its endothelial-specific ligand DLL4 have been evaluated immunohistochemically in a set of 63 cases of GBC. The results showed an aberrantly high expression of Notch receptors 1-3 in carcinomas and a significant association of cytoplasmo-nuclear coexistent localization of DLL4 expression with poor survival [98] ( Table 2).…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
“…Although this cancer is referred to as an orphan disease in the United States, GBC tumors affects many thousands of individuals worldwide, with the geographic areas with the highest mortality rates being Chile, Bolivia, Korea, Nepal, Bangladesh, Japan, Peru, Czech Republic and Slovakia [1]. Since the first description of the gallbladder carcinoma, studies have established a characteristic pattern of late diagnosis and ineffective treatment for this disease [2].…”
Section: Introductionmentioning
confidence: 99%